Povetacicept (ALPN-303; TACI vTD-Fc), an enhanced, potent dual inhibitor of BAFF and APRIL, ameliorates experimental autoimmune myasthenia gravis in C57BL/6N mice - Rinaldi, Elena; Puleo, Elisa; Consonni, Alessandra; Miglietti, Martina; Mantegazza, Renato; Wang, NingXin; Peng, Stanford L.; Lewis, Katherine E.; Dillon, Stacey R.; Baggi, Fulvio (Frontiers in Immunology, 2025)
Background and ObjectivesMyasthenia gravis (MG) is a T cell-dependent, B cell-mediated autoimmune disease targeting the acetylcholine receptor (AChR) and other proteins of the neuromuscular junction postsynaptic membrane. Production of pathogenic autoantibodies results from B cell activation and expansion of antibody-secreting cells, including plasma cells, whose differentiation and survival are reliant on the TNF family cytokines APRIL and BAFF. Povetacicept (ALPN-303; TACI vTD-Fc) is an Fc fusion protein of an engineered TACI domain with significantly more potent dual inhibition of APRIL and BAFF than wild-type (WT) TACI-Fc (e.g., telitacicept).MethodsIn this study, the activity of povetacicept was evaluated in the mouse experimental autoimmune MG (EAMG) model, compared to (i) telitacicept, (ii) a depleting anti-CD20 antibody, (iii) neonatal Fc receptor blocker efgartigimod, (iv) a matched Fc control protein, and (v) PBS as vehicle.ResultsTherapeutic administration of povetacicept ameliorated clinical manifestations in EAMG mice and was associated with significantly lower levels of immunoglobulin subclasses and anti-AChR antibody titers in serum, along with increased muscle AChR content – superior to the evaluated comparators. Povetacicept treatment also reduced the number of total B220+ and Ki67+ proliferating cells in draining lymph node follicles and resulted in modifications of splenic T and B cell subset frequencies, compared to controls.DiscussionThe potent, dual BAFF/APRIL inhibitor povetacicept significantly improves clinical disease activity in EAMG, associated with reductions in pathogenic anti-AChR autoantibodies and superior to comparator therapeutic interventions based on WT TACI-Fc, CD20 depletion, or FcRn inhibition. Povetacicept may therefore confer beneficial clinical outcomes in the treatment of MG and other autoantibody-related neurological diseases.